2019
DOI: 10.4274/imj.galenos.2018.80557
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice Regarding Type 2 Diabetes Mellitus Among Outpatients in a Health Center in East-Coast of Peninsular Malaysia

Abstract: Amaç: Tip 2 diabetes mellitus (T2DM) küresel bir salgın ve dünya nüfusu için bir tehdit haline gelimiştir. Yöntemler: Bu kesitsel çalışma, Doğu Malezya Yarımadası'ndaki bir sağlık merkezinin ayaktan başvuru yapan hastalarında T2DM ile ilgili bilgi, tutum ve uygulamaları arasındaki ilişkiyi (BTU) değerlendirmek amacıyla yapıldı. On sekiz yaşından büyük toplam 104 katılımcı araştırmacı tarafından rehberlik edilen ankete cevap vermek amacıyla örneklemeye seçilmiştir. Her bir BTU için toplam puanlar arasındaki ili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
1
0
0
Order By: Relevance
“…Among racial distribution, Chinese population ratio 152(45.10 %) was higher followed by Malays 137(40.65 %) and Indians 37(10.97 %). Besides that, 79.52 % have an average educational background, which is consistent with another study conducted in Malaysia [20] . The osteoporosis information, knowledge, understanding, and perception about exercise and calcium sources were poor (62.0 %).…”
Section: Discussionsupporting
confidence: 90%
“…Among racial distribution, Chinese population ratio 152(45.10 %) was higher followed by Malays 137(40.65 %) and Indians 37(10.97 %). Besides that, 79.52 % have an average educational background, which is consistent with another study conducted in Malaysia [20] . The osteoporosis information, knowledge, understanding, and perception about exercise and calcium sources were poor (62.0 %).…”
Section: Discussionsupporting
confidence: 90%
“…The views regarding the above finding are that all components of KAP and motivation are essential to ensure optimal diabetes control. 25 …”
Section: Discussionmentioning
confidence: 99%
“…This was comparable to findings by Salleh et al, where 99.1% agreed that exercise is essential for people with diabetes, but only a few engage in physical activities. 25 Also, Le Roux et al found that only a few participants are involved in regular exercise. 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation